Pengembangan dan Penerapan Modul Pembelajaran Pengoperasian Mesin CNC Milling untuk Meningkatkan Efektivitas Pembelajaran di Solo Technopark - Ananditho Panji Pratama; Ranto Ranto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This study aims to develop and implement a CNC machine operation learning module to improve learning effectiveness at Solo Technopark. The study is motivated by the absence of structured instructional materials that can support competency-based learning in CNC training, resulting in inconsistent learning processes and high dependence on instructors. This research employs a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observations, interviews, and questionnaires using a Likert scale, and analyzed using descriptive quantitative methods. The results indicate that the developed module achieved a high level of feasibility, as validated by material experts (87.5%) and media experts (84.30%). During the implementation stage, the module demonstrated an effectiveness level of 80.25%, categorized as effective. These findings suggest that the module enhances content clarity, supports self-directed learning, and improves participants’ skills in CNC machine operation. From a theoretical perspective, this study reinforces the role of modular learning in vocational education in promoting self-directed learning and consistency of competency acquisition (Putri & Widodo, 2023). However, limitations remain in terms of visual design and learning independence, indicating the need for further development.